Os juizados especiais federais como política pública e as recomendações do Banco Mundial no campo da justiça - Kataoka, Ieda (2015)
Considering the tripartite system that make up the state structure, the Judiciary began to be highlighted as a transformer of the political and social reality only in the last century, when he took a leading role in the consolidation of democratic regimes. Given the importance of the activity performed by him beyond the legal proceedings between the parties and the impact of the content of its decisions, it proved the need for the formulation of public policies in the area, triggering new studies, by lawyers and non-lawyers. Was awakened, furthermore, the interest of international spectators, who came to consider the justice system as one of the indicators to be weighted to assess the level of social and economic development of countries. This historic moment coincides with the process of economic and political integration among the countries in which a new concept of sovereignty began to be created. From this context, recommendations were drawn in the field of justice by the World Bank for the countries of Latin America and the Caribbean, in order to improve the provision of judicial activity, known as, efficiency, credibility, access to justice, transparency, independence and predictability, characterized by its interdisciplinary character, not just legal, and its public and private interface, for expressing the intentions of an international body set, primarily, that to balance the market relations. The objective of this study is to analyze the simplified procedure which was established by Law n. 10.259/2001, called Special Federal Courts, from the light of those recommendations. With consideration given to special rite, with different procedural tools the ordinary procedure and own principles, the approach to the Federal Special Courts in this work was the public policy of access to justice. The study was developed from the results released by the Federal Council of Justice, in 2012, research called "Access to Federal Court: ten years of Special Federal Courts". It was concluded from this data that, according to the World Bank's recommendations, the Special Courts Federal remain a model in evolution. Despite the large number of cases are filed each year and high productivity in the trials compared to the common law, it was found that some of the very institutions of the Courts have not yet been assimilated by the users, for example, the possibility to institute legal proceedings without a lawyer and the option for conciliation.